Humanistic aspect of communicative interaction in modern education - Ashytok, N. (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Introduction. Reforming education on humanistic principles is gaining importance in Ukraine. The emergence of the specified humanistic orientation of education is due to the formation of a humanistic "innovative society". A key factor for the successful progress of such a society is the presence of highly qualified personnel, on the level of competence (particularly in the field of communication) of which the well-being of the population depends. The aim and tasks. Understanding the specifics of communicative interaction in modern education from a humanistic point of view is the aim of the article, which is specified through the following tasks: to analyze the works that explore the specified process, to outline the problems that arise in its organization. Research methods. The theoretical and methodological basis of the study includes general scientific and special methods and approaches, through which communicative interaction in modern education will be studied from a humanistic aspect. One of these approaches is the competency-based approach. Research results. Humanism is currently considered a progressive ideology, and a sign of a high level of culture of a particular people. Humanism involves the recognition of universal human values as a priority in ensuring human rights, as well as the formation of a comprehensively developed personality. Improving the organization of education on a humanistic basis is possible only if there is communicative interaction, which contributes to the establishment of the individual as the highest social value. Education should be characterized by humanocentrism, which is ensured at the communicative level by changing the subject-object interaction into subjectsubject interaction. This interaction is characterized by the recognition of the student as an equal participant in educational activity, rather than as an object of the teacher's influence. Discussion. In the context of educating a humanistically oriented personality, the development of communicative competence should be promoted in the context of improving critical thinking and media literacy, as well as the cultivation of skills to counter disinformation. Conclusions. Humanistic communicative interaction with a subject-subject nature ensures the successful and effective implementation of the tasks of reforming Ukraine’s modern educational system. Therefore, it should be carried out in the context of professional training to form communicative competence in future teachers.